Personal Branding Evy Merdika to Build Public Perception on Instagram - Aji Prasojo; Imam Mukhlis (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The development of technology and information continues to grow to meet human needs, with the rapid development of technology and information on social media making it easier for people to improve their self quality, namely personal branding. Evy merdika carries out personal branding by using instagram as a medium to build good public perception. Instagram is used to facilitate communication with the public with the character they have, as well as forming a personal branding about themselves. This research uses a qualitative approach with a descriptive research type. Data collection techniques use primary data and secondary data, primary data is carried out through direct interviews with evy merdika as the informant, secondary data through documentation, documents in research using photos, articles in instagram account uploads. The results of personal branding research conducted by evy merdika on her instagram account, @evymerdika, show that evy merdika builds a good public perception and provides inspiration for the younger generation to continue creating, working and getting a good education. The results of this research show that evy merdika focuses on one area of professionalism, public speaking skills, and the ability to organize events. Based on public perception, evy merdika is described as a woman who is passionate about achieving a better life through work, hobbies and the business she has built. Personal branding on instagram shows how evy merdika carries out daily activities to show her value to other people, so that people can trust her more.